1999
DOI: 10.1002/(sici)1097-4547(19990315)55:6<724::aid-jnr7>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive protein phosphatase activity regulates the phosphorylation state of p38 protein kinase in primary astrocyte culture

Abstract: Reactive oxygen species (ROS) have been implicated as second messengers that activate protein kinase cascades, although the means by which ROS regulate signal transduction remains unclear. In the present study, we show that interleukin 1beta (IL1beta), H2O2, and sorbitol-induced hyperosmolarity mediate a 5- to 10-fold increase in phosphorylation (activation) of the p38 protein kinase in rat primary glial cells as measured by analyses of Western blots using an antibody directed against the dually phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…After PC12 cells were pretreated with SB203580 prior to exposure to CoCl 2 , CoCl 2 -induced ROS production was markedly blocked, suggesting that p38MAPK may be a positive regulator for CoCl 2 -induced ROS production in PC12 cells. Previous studies reported that ROS appeared to be upstream of p38MAPK (33). However, based on our results, ROS and p38MAPK may locate at a parallel level, and there is interaction between ROS and p38MAPK during CoCl 2 -induced neuronal injuries.…”
supporting
confidence: 44%
“…After PC12 cells were pretreated with SB203580 prior to exposure to CoCl 2 , CoCl 2 -induced ROS production was markedly blocked, suggesting that p38MAPK may be a positive regulator for CoCl 2 -induced ROS production in PC12 cells. Previous studies reported that ROS appeared to be upstream of p38MAPK (33). However, based on our results, ROS and p38MAPK may locate at a parallel level, and there is interaction between ROS and p38MAPK during CoCl 2 -induced neuronal injuries.…”
supporting
confidence: 44%
“…In particular, p38 and JNK have critical roles in the inflammatory response and are regulated by various pro-inflammatory cytokines [42,43] and ROS [56,60]. To assess the effects of ROS on intracellular signaling, we evaluated P2X 7 agonist-initiated events following treatment of cells with the anti-oxidants ascorbic acid and NAC, which function by increasing intracellular glutathione and reducing oxidized proteins [57].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤ has been found to elicit H 2 O 2 synthesis in rat primary astrocytes [16] and IL-1␤ mRNA is increased by NADPH oxidase-derived ROS in rat primary astrocyte and microglia cultures [14]. Cortical COX-2 has also been reported to be markedly increased, and high levels of ROS generated in response to a high fat diet, suggesting a neural inflammatory response [32].…”
mentioning
confidence: 99%